Spiro-thiophene derivatives as hole-transport materials for perovskite solar cells1. Issue 23 (21st June 2015) - Ma, Shuying; Zhang, Hua; Zhao, Ning; Cheng, Yibing; Wang, Mingkui; Shen, Yan; Tu, Guoli
<x xml:space="preserve">Abstract</x> Spiro-thiophene derivatives act as promising hole transport materials for highly efficient perovskite solar cell application.